Women with Attention Deficit Hyperactivity Disorder and Perinatal Distress: A Literature Review - ANTONIOU, EVANGELIA; Papatrechas, Alexandros; Orovou, Eirini (International Journal of Innovative Research in Medical Science, 2022)
Although the childbirth is considered a pleasant experience in a woman's life, there are cases that the mental health and well-being of mother is affected. On the other hand, women with Attention-Deficit/Hyperactivity Disorder are more likely than men to have one or more comorbidities, including schizophrenia, autism spectrum disorder, suicidal behavior, depression, bipolar and tic disorders. This increased risk suggests that women are a more vulnerable population during the perinatal period. The aim of this study was to determine the effect of Attention-Deficit/Hyperactivity Disorder symptomatology on women's mental health status during the perinatal period, through an investigation of the literature. These studies found that throughout the perinatal period, women with Attention-Deficit/Hyperactivity Disorder are more at risk of developing perinatal stress, especially during postpartum period and highlights the need for more research on perinatal mental health and the need also for a pregnancy screening program in the general pregnant population as well as in pregnant women suffering from ADHD.